Pengaruh Layanan Bimbingan Kelompok Dengan Teknik Brainstorming Untuk Meningkatkan Komunikasi Antar Pribadi Siswa Kelas XI SMAN 4 Kota Jambi - Susanti, Marselina; Yulianti, Yulianti; Rahman, K.A (Universitas Pahlawan Tuanku Tambusai, 2024)
Interpersonal communication is a tool for and interaction in the school environment. The phenomenon at SMAN 4 Jambi City, students with low interpersonal communication skills such as students who close themselves off when discussing in class or counseling, are withdrawn, nervous when communicating, act indifferent and use dirty words when speaking. This research aims to reveal the influence of providing brainstorming technique group guidance services on students' interpersonal communication. This type of quantitative research, semi-experimental one group pretest-posttest method. The research population was class XI students. The number of samples was 8 with a purposive sampling technique, the data was processed using SPSS version26. The research results before treatment were 96 and after treatment were 107.8. The t-test result for t-count is 5,569 which is greater than t-table 2,306. Thus, group guidance services using brainstorming techniques can influence the level of interpersonal communication of students at SMAN 4 Jambi City